Migration and families left behind - Sylvie Démurger (IZA World of Labor, 2015)
About a billion people worldwide live and work outside their country of birth or outside their region of birth within their own country. Labor migration is conventionally viewed as economically benefiting the family members who are left behind through remittances. However, splitting up families in this way may also have multiple adverse effects on education, health, labor supply response, and social status for family members who do not migrate. Identifying the causal impact of migration on those who are left behind remains a challenging empirical question with inconclusive evidence.
Keywords: O15; F22; I15; I25; J13; 330; labor migration; sending communities; left-behind population; developing economies